Racisme et xénophobie dans la favela ? Deux temps de la présence d’immigrés angolais à Maré (Rio de Janeiro) - Nicolas Quirion (Cahiers des Amériques Latines)
In this paper, we focus on the settlement of a group of Angolan immigrants in the favelas of Maré in Rio de Janeiro. Based on a participant observation work carried out from the places of sociability of the Angolans, we examine the nature of the relations that have been established between this foreign group and the Brazilian residents of the favela. In an informal and marginalized urban space strongly marked by structural racism and where the relationship to Africanity remains ambiguous, the presence of immigrants from a Sub-Saharan African country allows us to take a new look at ethno-racial relationships and identity reconstructions in Brazil.